Bridget Wilder, spy-in-training - Bernstein, Jonathan ca. 20. Jh (Katherine Tegen Books, 2015)
"An adopted middle child receives an unexpected package on an otherwise unremarkable birthday inviting her to join a super-secret division of the CIA"...
Keywords: Spies; Family life; Middle-born children; Adoption; Jugendbuch